(untitled) (KUTTAB, 2024)
Early childhood is a golden period of development. Early childhood education must be carried out properly and optimally, includes Jumâ€™at prayer education. Parents must understand how to get children do Jumâ€™at prayers. Through behavioral learning theory, parents can easily condition the habit of Jumâ€™at prayers. This study aims to explore in depth how behavioral learning theory influences the habit of Jumâ€™at prayers in early childhood. This study uses a descriptive qualitative design through interview, observation and documentation methods. This study is a behavioral learning theory through stimulus and response can effectively train children to perform Jumâ€™at prayers. This learning theory can also train children’s responsibility, discipline, readiness to do something, love for religion and invite children to like to give alms.